Metabolic quirks and the colourful history of the Euglena gracilis secondary plastid - Novák Vanclová, Anna M G; Zoltner, Martin; Kelly, Steven; Soukal, Petr; Záhonová, Kristína; Füssy, Zoltán; Ebenezer, ThankGod E; Lacová Dobáková, Eva; Eliáš, Marek; Lukeš, Julius; Field, Mark C; Hampl, Vladimír (The New phytologist, 2020)
Euglena spp. are phototrophic flagellates with considerable ecological presence and impact. Euglena gracilis harbours secondary green plastids, but an incompletely characterised proteome precludes accurate understanding of both plastid function and evolutionary history. Using subcellular fractionation, an improved sequence database and MS we determined the composition, evolutionary relationships and hence predicted functions of the E. gracilis plastid proteome. We confidently identified 1345 distinct plastid protein groups and found that at least 100 proteins represent horizontal acquisitions from organisms other than green algae or prokaryotes. Metabolic reconstruction confirmed previously studied/predicted enzymes/pathways and provided evidence for multiple unusual features, including uncoupling of carotenoid and phytol metabolism, a limited role in amino acid metabolism, and dual sets of the SUF pathway for FeS cluster assembly, one of which was acquired by lateral gene transfer from Chlamydiae. Plastid paralogues of trafficking-associated proteins potentially mediating fusion of transport vesicles with the outermost plastid membrane were identified, together with derlin-related proteins, potential translocases across the middle membrane, and an extremely simplified TIC complex. The Euglena plastid, as the product of many genomes, combines novel and conserved features of metabolism and transport.
Keywords: metabolic reconstruction; proteome; přenos genů horizontální; lateral gene transfer; biologická evoluce; plastidy; shopping bag hypothesis; protein import; proteom; Euglena gracilis; Proteome; Proteins; plastid; Gene Transfer, Horizontal; regulace genové exprese; SUF pathway; proteiny; Plastids; Gene Expression Regulation; Biological Evolution